Solve and check result: 8x + 4 = 3(x - 1) + 7

Asked by Aaryan | 1 year ago |  97

##### Solution :-

8x + 4 = 3(x - 1) + 7

8x + 4 = 3x - 3 + 7

Transposing 3x to L.H.S and 4 to R.H.S, we obtain

8x - 3x = - 3 + 7 - 4

5x = - 7 + 7

x = 0

L.H.S = 8x + 4 = 8 × (0) + 4 = 4

R.H.S = 3(x - 1) + 7 = 3 (0 - 1) + 7 = - 3 + 7 = 4

L.H.S. = R.H.S.

Hence, the result obtained above is correct.

Answered by Sakshi | 1 year ago

### Related Questions

#### Solve the inequations and graph their solutions on a number line  – 1 < (x / 2) + 1 ≤ 3, x ε l

Solve the inequations and graph their solutions on a number line  – 1 < ($$\dfrac{x}{2}$$) + 1 ≤ 3, x ε l

#### Solve the inequations and graph their solutions on a number line – 4 ≤ 4x < 14, x ε N

Solve the inequations and graph their solutions on a number line – 4 ≤ 4x < 14, x ε N

#### Solve (x / 3) + (1 / 4) < (x / 6) + (1 / 2), x ε W. Also represent its solution on the number line.

Solve ($$\dfrac{x}{3}$$) + ($$\dfrac{1}{4}$$) < ($$\dfrac{x}{6}$$) + ($$\dfrac{1}{2}$$), x ε W. Also represent its solution on the number line.

If the replacement set is {-3, -2, -1, 0, 1, 2, 3}, solve the inequation $$\dfrac {(3x – 1) }{2} < 2$$. Represent its solution on the number line.
Solve the inequations ($$\dfrac{3}{2}$$) – ($$\dfrac{x}{2}$$) > – 1, x ε N